BRAND EXPERIENCE IN BUILDING LOYALTY THROUGH THE SATISFACTION AND TRUST IN ENERGY DRINK (CASE IN INDONESIA) - Dharviandi, Taufiek (Universitas Esa Unggul, 2016)
AbstractEnergy drink industry is growing rapidly in Indonesia. There are various brands, packaging (whether in bottle or sachet) and the liquid and powder types. This growth also creates competition in the energy drink business where energy drink manufacturers continuously strive in various ways so that customers remain loyal to its products. The objective of this study is to research the role of brand experience that is mediated by brand trust and brand satisfaction on the energy drink of Kratingdaeng brand. The design of this study was used explanatory research with survey method by distributing questionnaires in which there are 27 statements with Likert scale 5 to 210 consumers Kratingdaeng in five major cities in Indonesia as a sample. The data analysis technique that has been collected using Structural Equation Modeling (SEM), assisted by calculation process with LISREL. In a study conducted five hypotheses, then it can be shown that the scale is reliable and valid, to the brand experience, brand loyalty, brand satisfaction and brand trust. The result of T values greater than t table (t>1.96) and significant values (p<0.05), then the brand experience to positively influence in building brand loyalty, both directly and indirectly through brand satisfaction and brand trust.Keywords: brand loyalty, brand experience, brand trust, brand satisfaction.